Social support, resource utilization, and well-being: a survey of adolescent parents in Washington, DC - Yael Smiley; Jaytoya Manget; John Barber; Iana Clarence; Nkechi Enwerem; Christiana Jolda; Patricia Quinn; Zillah Jackson Wesley; Davene White; Binny Chokshi (BMC, 2023)
Abstract Background Adolescent parents experience worse health and socioeconomic outcomes compared to older parents. Little is known about the factors that can lead to better health and well-being among teen-headed families. A city-wide collaborative conducted a comprehensive well-being assessment of expectant and parenting teens in Washington, DC. Methods An online, anonymous survey was conducted with adolescent parents in Washington, DC, using convenience sampling. The survey consisted of 66 questions adapted from validated scales of quality of life and well-being. Descriptive statistics were used to describe the data overall, by subgroups of mother and father, and by subgroups of parent age. Spearman's correlations were utilized to demonstrate associations of social supports with well-being metrics. Results A total of 107 adolescent and young adult parents from Washington, DC, completed the survey; 80% of respondents identified as mothers and 20% as fathers. Younger adolescent parents rated their physical health better compared to older adolescent and young adult parents. Adolescent parents reported accessing various governmental and community-based resources in the preceding 6 months. The most used resources were supplemental food programs, with 35% receiving Supplemental Nutrition Assistance Program benefits and 24% receiving support from the Special Supplemental Nutrition Program for Women, Infants and Children. There was no significant difference in health-related well-being metrics among those who did and did not receive resources. Having higher self-reported social support was positively correlated with higher self-rated physical health, mental health, and well-being, as well as experiencing positive emotions, and was negatively correlated with experiencing negative emotions. Conclusion This snapshot of the well-being of expectant and parenting teens in Washington, DC, showed overall positive physical, mental, and emotional health. Greater social support was correlated with better outcomes in these areas. Future work will leverage the multidisciplinary collaborative to translate these findings into policies and programs that meet the needs of this population.